(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Access to quality healthcare can often be expensive even in advanced countries. That is why governments all over the world have introduced one form of health insurance or the other. However, there seems to be below par utilization of the National Health Insurance Scheme (NHIS) in Nigeria. This study seeks to examine the influence of patients’ perception on utilization of National health insurance services in three selected (District hospitals) in AMAC, FCT, Abuja. This study adopts the descriptive survey research design. The population of this study comprised the enrollees of AMAC District hospitals, FCT, Abuja. A sample of three hundred and eight five (385) enrollees of the three district hospitals were selected using simple random sampling. A structured questionnaire was used to collect quantitative data which was analyzed using both descriptive and inferential statistics. Response rate = 79% and about 56.6% of the respondents were Females, ages 25-35 with 72.5% being married. The majority of respondents were Christians with 66.8%, 30% were Muslims and the remaining 2.9% were others. Most respondents were BSc/HND holders with 58.9%, MSc 6.6%, ND 24.75, and the remaining 9.9% were school cert holders. About 53% of respondents enjoy the health insurance because they enjoy medical care from well trained personnel. More than 50% of the respondents feel that the Nurses and Doctors do not treat patients with respect and they considered the waiting time very high. The majority of respondents also feel that they are not being treated according to NHIA operational guidelines, and that the cash paying patients are treated better. There was a significant influence of patients’ perception on utilization of health insurance services. The Perception of health insurance among the enrollees of AMAC district hospitals varied while the utilization was fair enough.